Sex role stereotyping in first grade and pre-vocational junior high school students: An attitudinal study - Jack, Deloris A.; Fitzsimmons, George (Canadian Journal of Counselling and Psychotherapy, 2012)
Twenty-four girls and twenty-four boys in grade one and thirty girls and thirty boys in prevocational ninth grade class were presented with a list of 35 occupations and activities. Students responded by indicating woman, man or either. The results revealed that both first grade and ninth grade boys have very stereotyped views of occupations. Overall ninth grade girls are willing to accept both women and men in non-traditional roles. First grade girls hold stereotyped views, however they are receptive to some non-traditional roles. Implications for vocational counselling are presented.